The Concept of the Science of Religions and Its Origins in Islamic and Western Thought - Ali Zalmat (Penerbit Hellow Pustaka, 2024)
The researcher in this study delved into the evolution and conceptual delineation of the science of religions, employing an analytical and descriptive historical approach. It was concluded that this academic discipline involves the study of the emergence, progression, and dissemination of various belief systems, their doctrines, rituals, and legal frameworks, while also undertaking comparative analyses to underscore both distinctions and parallels. This field, rooted in Islamic tradition, garnered Western interest due to several factors, particularly the impact of Islamic civilization on Western civilization.